Composite cement soil prepared from seawater, nano silicon dioxide and polyvinyl alcohol fiber and preparation method of composite cement soil

By using composite materials of seawater, nanosilicon dioxide and polyvinyl alcohol fibers in cement soil, the problems of resource shortage and insufficient strength in coastal areas are solved, high-strength, cracking and corrosion resistance are achieved, and environmental pollution risks are reduced.

CN119822734AActive Publication Date: 2025-04-15HUBEI UNIV OF TECH
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202510043643.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-10
Publication Date
2025-04-15
Estimated Expiration
2045-01-10

AI Technical Summary

Technical Problem

In remote coastal areas and island reef areas, a large amount of fresh water is consumed during the production process of traditional cement mixing piles, resulting in resource shortage and high costs. At the same time, the cement soil is prone to cracking and deteriorating, insufficient strength and environmental pollution problems.

Method used

By using composite cement soil prepared by seawater, nanosilicon dioxide and polyvinyl alcohol fibers, the material ratio and preparation method are optimized to form high-strength, crack-resistant and corrosion-resistant cement soil.

Benefits of technology

It significantly reduces dependence on freshwater resources, improves the mechanical strength and service life of cement soil, enhances corrosion resistance and crack resistance, reduces the risk of environmental pollution, and improves the economic benefits of construction.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119822734A_ABST
    Figure CN119822734A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of cement soil preparation, and particularly relates to composite cement soil prepared from seawater, nano silicon dioxide and polyvinyl alcohol fiber and a preparation method of the composite cement soil, and the composite cement soil is prepared from 63-70% of dry soil powder, 9-10% of Portland cement, 1.8-2.2% of nano silicon dioxide, 0.6-1.2% of polyvinyl alcohol fiber, 0.2% of dispersing agent and 16.4-25.4% of seawater. According to the composite cement soil, dependence on fresh water resources can be remarkably reduced, the problem of deterioration caused by fatigue cracks due to seawater corrosion and long-term periodic load can be effectively solved, accordingly, the mechanical strength of a cement soil foundation is remarkably improved, the service life of the cement soil foundation in the coastal environment is prolonged, and high economic benefits are achieved. Through the synergistic effect of the nano silicon dioxide and the polyvinyl alcohol fiber, the mechanical property, the crack resistance and the seawater corrosion resistance of the cement soil are remarkably enhanced, and the brittle failure of the cement soil is effectively inhibited, so that the cement soil can be stably applied to coastal soft soil foundation reinforcement projects for a long time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of cement soil preparation, and in particular relates to a composite cement soil prepared from seawater, nano silicon dioxide and polyvinyl alcohol fiber and a preparation method thereof. Background Art

[0002] The mixing water required in the production process of traditional cement mixing piles consumes a large amount of fresh water, and if the water used for cooling, washing, energy and transportation is taken into account, the fresh water consumption in the entire manufacturing process will be several times more. In remote coastal areas and islands where fresh water resources are scarce, long-distance transportation of fresh water not only leads to a significant increase in costs, but also increases energy consumption. In addition, in order to cope with the shortage of fresh water, a temporary water supply system needs to be established, which not only prolongs the construction time, but may also cause unnecessary delays during the construction process.

[0003] In the coastal port traffic road bases in remote coastal areas and island reef areas, cement soil is subjected to long-term cyclic loads (such as traffic vehicles or machine vibrations) and the corrosive ions in seawater gradually erode the cement-based materials, which may gradually form fatigue cracks. Although these cracks may have little effect on the overall structure of the cement soil foundation in the short term, under the coupling of long-term cyclic loads and corrosion degradation, the tiny cracks will gradually expand and penetrate, eventually leading to pile damage, seriously endangering normal use and project safety. Although increasing the cement content can alleviate these problems to a certain extent, it may cause new problems such as uneven strength of the cement soil foundation, extended maintenance cycle and increased brittleness. These problems will not only increase the difficulty and cost of construction, but also significantly reduce the safety of the cement soil foundation. In addition, large-scale production of cement will also lead to a large amount of CO 2 Therefore, solving the problems of easy cracking, easy deterioration, insufficient strength and environmental pollution of cement soil is the key to achieving its long-term and stable application in coastal areas and island and reef areas.

[0004] At present, there are some solutions to the above problems. For example, patent CN103539389B provides a method for preparing cement soil using seawater, which reduces the amount of fresh water used by replacing fresh water with seawater and inhibits the influence of corrosive ions in the ocean. However, this method has limited effect in improving the strength of cement soil, and does not take into account the defect that cement soil is prone to cracking when subjected to cyclic loads, which will accelerate its deterioration process. In addition, this technology requires the addition of a large amount of corrosion inhibitors, which not only increases construction time and cost, but may also bring certain safety hazards. "Nano-SiO 2"Improved Dynamic Elastic Modulus and Damping Ratio Test of Cement Soil" (Engineering Science and Technology, Zhuang Xinshen et al., 2024) and patent CN112851247B disclose a method of improving the seawater corrosion resistance and fatigue performance of cement soil by adding nano-silicon dioxide to it. However, this method also exacerbates the tendency of cement soil to undergo brittle failure when subjected to extreme loads in a seawater environment, which may cause major safety hazards. Patent CN114292080A and "Bending and Early Crack Resistance of Cement Soil Reinforced with Jute and Polyvinyl Alcohol Fibers" (Bulletin of Silicates, Yao Xin et al., 2021, 40(09)) disclose a method of using polyvinyl alcohol fibers to improve the crack resistance of cement soil and prevent brittle failure. However, this method has limited effect in improving the strength of cement soil, and the use of polyvinyl alcohol fibers alone is greatly restricted in a seawater environment.

[0005] Therefore, how to provide a corrosion-resistant cement soil that uses seawater as a water source and has high strength, high durability and high safety has become a technical problem that needs to be solved urgently. Summary of the invention

[0006] The object of the present invention is to provide a composite cement soil prepared by seawater, nano-silicon dioxide and polyvinyl alcohol fiber and a preparation method thereof, and by optimizing the formula, high-strength, crack-resistant and corrosion-resistant cement soil is obtained using seawater as a water source.

[0007] To achieve the above-mentioned object, the present invention provides a composite cement soil prepared by seawater, nano-silicon dioxide and polyvinyl alcohol fiber, wherein the raw materials include, by mass percentage, 63% to 70% of dry soil powder, 9% to 10% of silicate cement, 1.8% to 2.2% of nano-silicon dioxide, 0.6% to 1.2% of polyvinyl alcohol fiber, 0.2% of dispersant and 16.4% to 25.4% of seawater.

[0008] Furthermore, the particle size of the nano-silicon dioxide is 20±5nm, and the specific surface area is 160-190m 2 / g.

[0009] Furthermore, the length of the polyvinyl alcohol fiber is 6±1 mm, the equivalent diameter is 16±1 μm, and the density is 1.29±0.1 g / cm 3 .

[0010] Furthermore, the mass ratio of sea salt to clean water in the seawater is (32-38):1000, preferably 35:1000. In actual engineering, the pre-seawater treatment process is as follows: first, extract seawater, perform the first step of filtration operation through a large grid, and then use a small grid for the second step of filtration. Subsequently, the seawater after two filtrations is introduced into a sedimentation tank for sedimentation treatment. When there is no obvious floating matter in the seawater, the supernatant is introduced into a reservoir, and the pre-treatment of the seawater is completed.

[0011] Further, the dispersant is polyvinyl pyrrolidone K30;

[0012] And / or, the silicate cement is P.O42.5 silicate cement.

[0013] Furthermore, the dry soil powder is obtained by evenly spreading the original soil sample collected at a depth of 15±1m underground and placing it outdoors for natural evaporation for 40-50 hours. After natural evaporation, the soil sample is crushed and placed in an oven at 105±5°C for drying for 20-30 hours, then taken out and cooled, and sieved through a 2mm sieve to obtain dry soil powder.

[0014] The present invention also provides a method for preparing the composite cement soil prepared from seawater, nano-silicon dioxide and polyvinyl alcohol fiber as described in any one of the above, the preparation steps being as follows:

[0015] (1) Weigh dry soil powder, polyvinyl alcohol fiber, nano-silicon dioxide, cement and dispersant according to the proportion, and then stir in a mixer for 6-8 minutes until the mixture is uniform;

[0016] (2) Weigh the required amount of seawater, pour it into the mixture in the mixer, and continue stirring for 10-12 minutes until the mixture forms a uniform cement slurry;

[0017] (3) pouring the evenly mixed cement slurry into the mold. During the grouting process, the mold is placed on a vibration table to keep vibrating until the mold is filled with cement slurry and bubbles are removed;

[0018] (4) After curing at 20°C ± 2°C for 48 hours, demoulding is performed to obtain composite cement soil.

[0019] Furthermore, the mold is a cylindrical transparent plastic mold with a diameter of 39 mm and a height of 78 mm.

[0020] Furthermore, the polyvinyl alcohol fibers are dispersed using ultrasonic vibration screen processing technology before being added.

[0021] The present invention also provides an application of the composite cement soil prepared from seawater, nano silicon dioxide and polyvinyl alcohol fibers, which is used for the preparation of coastal transportation roadbeds and pile foundations in coastal areas and island and reef areas.

[0022] The present invention uses seawater instead of fresh water to prepare composite cement soil, and effectively solves the practical engineering problem of fresh water resource shortage in remote island and reef areas by using local materials.

[0023] Compared with the prior art, the above technical solution conceived by the present invention mainly has the following technical advantages and beneficial effects:

[0024] 1. In view of the shortcomings of existing seawater cement soil reinforcement schemes, such as poor corrosion resistance, poor crack resistance, low strength growth rate and brittle failure, the composite cement soil prepared by seawater, nano-silicon dioxide and polyvinyl alcohol fiber provided by the present invention effectively solves the above problems. By adding nano-silicon dioxide and polyvinyl alcohol fiber composite materials, the hydration reaction of cement can be improved, and the good combination of fiber and cement soil matrix can be promoted, thereby giving full play to the reinforcing effect of nano-silicon dioxide and fiber. The present invention significantly reduces the dependence on fresh water resources, effectively solves the problem of fatigue cracks caused by seawater corrosion and long-term periodic loads, and greatly improves the mechanical strength and service life of cement soil in coastal environments.

[0025] 2. In the composite cement soil of the present invention, nano-silicon dioxide and its promoted hydration products effectively fill the internal pores of the cement soil, greatly enhancing the linkage between the fiber and the cement soil matrix, thereby inhibiting the corrosion of the internal structure of the cement soil by seawater, and effectively improving the deformation and settlement problems of the cement soil in the coastal environment. The present invention has the advantages of reliable technology, reasonable design, no environmental pollution, strong adaptability and convenient construction.

[0026] 3. The present invention has determined the optimal material ratio and preparation method of cement soil prepared based on seawater, nano-silicon dioxide and polyvinyl alcohol fiber composite materials through a large number of experiments. Only by adopting the optimal dosage and preparation method of the present invention, the strength growth rate of the composite cement soil prepared by nano-silicon dioxide and polyvinyl alcohol fiber can exceed the sum of the strength growth rates of cement soil mixed with fiber alone and cement soil mixed with nano alone, and achieve the best curing effect, thereby meeting the requirements of long-term mechanical stability of the project.

[0027] 4. The composite cement soil of the present invention provides a new technical idea and reference for the construction of coastal transportation roadbeds and pile foundations in remote coastal and island and reef areas. The composite use of nano-silicon dioxide and polyvinyl alcohol fiber in cement soil is the first time. The improvement effect and economic benefits of the polyvinyl alcohol fiber on cement soil in seawater environment are significantly better than similar materials such as glass fiber, basalt fiber, steel fiber and polypropylene fiber. As a hydrophilic fiber, polyvinyl alcohol fiber has a stronger bonding force with cementitious materials and performs well in compression ductility, effectively reducing the risk of brittle failure of cement soil.

[0028] Compared with the prior art, the technical solution proposed by the present invention has the following advantages:

[0029] Compared with the "Patent CN103539389B Preparation Method of Seawater Mixed Cement Soil", the present invention does not take into account the defect that cement soil is prone to cracking when subjected to cyclic loads, which will accelerate its deterioration process and the technology requires the addition of a large amount of corrosion inhibitors. The addition of a large amount of corrosion inhibitors may form too many pores or microcracks in the cement soil, which not only reduces the impermeability, but also may change the pore structure of the cement soil, increase its porosity, change the pore size distribution, and increase the number of macropores. This will not only affect the mechanical properties and durability of the cement soil, but also the corrosion inhibitor may contain some environmentally harmful chemicals, such as heavy metal ions, organic matter, etc. When the cement soil is affected by rain erosion or other natural factors during use, these harmful substances may be gradually released, causing pollution to the surrounding soil and water environment, affecting the ecological balance. At the same time, the patent also has the defects of low strength and poor durability of cement soil. In view of the fact that the existing seawater cement soil reinforcement scheme cannot be directly applied and has shortcomings, the reinforced cement soil material selected in the present invention has greater advantages. By adding nano-silica and polyvinyl alcohol fiber composite materials to cement soil, the addition of polyvinyl alcohol fiber can further enhance the strength and effectively improve the anti-cracking performance of cement soil.

[0030] The present invention is related to "Nano-SiO 2 Improved cement soil dynamic elastic modulus and damping ratio test" (Engineering Science and Technology, Zhuang Xinshan et al., 2024) and "Patent CN112851247B A nano cement soil resistant to seawater corrosion and its preparation method", the price of using nano-silicon dioxide alone to improve cement soil is higher, and the crack resistance of using nano-silicon dioxide alone to improve cement soil is poor, which aggravates the tendency of cement soil to undergo brittle failure when subjected to extreme load in seawater environment, which may cause major safety hazards. The present invention adds cement soil prepared by adding nano-silicon dioxide and polyvinyl alcohol fiber composite materials, and the fiber in the composite cement soil The surface is wrapped by more and denser calcium silicate gel, thereby enhancing the mechanical interlocking effect of the materials between the fiber and the hydration product. When the fiber is compressed, the pointed soil particles exert pressure on the fiber surface to form a dent structure. The incorporation of nano-silicon dioxide can effectively prevent the sliding and reorganization of soil particles, and further increase the roughness of the fiber surface. The present invention greatly enhances the mechanical interlocking effect between the fiber and the hydration product, and the capillary structure filled with cement soil enhances the internal structure, thereby preventing the internal structure from being corroded by seawater, greatly enhancing the corrosion resistance, crack resistance and mechanical strength of the cement soil, and reducing the required cost.

[0031] Compared with patent CN114292080A and "Bending and early crack resistance of jute and polyvinyl alcohol fiber reinforced cement soil" ("Silicate Bulletin", Yao Xin et al., 2021, 40(09)), although polyvinyl alcohol fiber can improve the tensile strength and toughness of cement soil to a certain extent, the effect of improving the compressive strength of cement soil is relatively limited. The disadvantage of adding polyethylene fiber alone is that when the hydration product is insufficient, it is difficult for the fiber to form an effective bond with the cement soil matrix, thereby limiting the full play of the fiber function. In some engineering applications that require high compressive strength of cement soil, such as foundation bearing layers, the engineering requirements may not be met. In view of the defect of the patent that the fiber function cannot be fully exerted, the present invention can effectively improve the hydration reaction of cement by incorporating nano-silica, promote the good combination of fiber and cement soil matrix, and thus give full play to the reinforcing effect of fiber. The present invention has also found, through a large number of experiments, a cement soil based on seawater, nano-silicon dioxide and polyvinyl alcohol fiber composite material configuration. Through the optimal material ratio and production method, the cement soil curing strength is improved to meet the long-term mechanical stability requirements of the project. The present invention has the advantages of reliable and reasonable technology, no environmental pollution, strong adaptability and convenient construction.

[0032] The present invention also conducts an in-depth feasibility analysis on the erosion and damage of cement soil by corrosive ions in seawater:

[0033] The composite addition of nano-silica and polyvinyl alcohol fiber makes the cement soil structure more compact, preventing the intrusion of chemical erosion media. At the same time, both of them have a certain chemical stability, which can improve the resistance of cement soil to chemical substances such as acids, alkalis and salts to a certain extent. The combined effect of the two significantly improves the impermeability of cement soil and reduces the risk of erosion of cement soil by external moisture, salt, etc. Polyvinyl alcohol fiber can limit the shrinkage and deformation of cement soil and reduce the occurrence of shrinkage cracks. The filling effect of nano-silica also helps to reduce the shrinkage rate of cement soil. The synergistic effect of the two effectively controls the formation and development of cement soil cracks.

[0034] In summary, the present invention effectively solves the defects faced by the prior art. And through a large number of experiments, the optimal ratio of fiber and nano-silica is determined to avoid affecting the performance of the combined application of the two due to excessive or insufficient addition. The strength growth rate of the composite cement soil prepared with nano-silica and polyvinyl alcohol fiber can exceed the sum of the growth rates of single fiber-doped cement soil and single nano-doped cement soil. Only by using the material with the optimal dosage determined by the present invention and the corresponding preparation method can the best curing effect be achieved. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 This is a schematic diagram of the distribution of the nano-silicon dioxide and fibers in the composite cement soil of the present invention;

[0036] Figure 2 It is a schematic diagram of the microscopic interface mechanics of nano-silica and fiber in the composite cement soil of the present invention.

[0037] Reference numerals

[0038] 1-universal testing machine, 2-cement soil, 3-fiber, 4-stress around fiber, 5-pore water, 6-indentation on fiber surface, 7-friction and cohesion between fiber and hydration product, 8-pore, 9-hydration product of nano-silica, 10-fiber breakage, 11-soil particles, 12-matrix, 13-tensile stress, 14-pointed soil particles, 15-resistance provided by nano-particles and hydration products, 16-soil particle rotation; 21-fiber, 22-nano-silica is added, 23-fiber pull-out state, 24-pores and pore water filled with nano-silica, 25-fiber breakage. DETAILED DESCRIPTION

[0039] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0040] The technical problem to be solved by the present invention is how to achieve local materials, overcome the influence of corrosive ions in seawater during application, ensure that the prepared cement soil has high strength, and significantly improve its service life and safety. To this end, the present invention provides a composite cement soil prepared by seawater, nano-silicon dioxide and polyvinyl alcohol fiber, and its raw materials include by mass percentage: 63% to 70% dry soil powder, 9% to 10% silicate cement, 1.8% to 2.2% nano-silicon dioxide, 0.6% to 1.2% polyvinyl alcohol fiber, 0.2% dispersant and 16.4% to 25.4% seawater. In remote island and reef areas, it can not only significantly reduce the dependence on freshwater resources, but also effectively solve the deterioration problem caused by fatigue cracks caused by seawater corrosion and long-term periodic loads, thereby significantly improving the service life of cement soil foundation in coastal environments and greatly enhancing the corrosion resistance, crack resistance and mechanical strength of cement soil. The method uses local materials, has simple process, convenient operation, excellent economic benefits, and can effectively meet actual production needs.

[0041] Combination Figure 1 and Figure 2 It can be seen that the principles of crack resistance and corrosion resistance of the present invention are as follows:

[0042] Polyvinyl alcohol fiber improves the crack resistance of cement soil and inhibits brittle failure through the bonding force between it and the cement soil matrix; nano-silica relies on its volcanic ash activity and nucleation effect to promote cement hydration, thereby enhancing the mechanical properties and corrosion resistance of cement soil. However, when cement soil with only added fibers breaks during loading, the pores and pore water around the fibers will weaken the friction resistance between the matrix and the fibers, making it lower than the tensile stress borne by the fibers, causing the fibers to slide and pull out easily, losing the "bridge" function of connecting the cracks in the cement soil. In addition, the fracture of the fibers due to the lack of effective matrix wrapping is also one of the main reasons for further reducing the strength of cement soil.

[0043] The present invention can effectively solve the above problems by adding polyvinyl alcohol fiber and composite cement soil prepared by nano-silicon dioxide. When the fiber is compressed, its surface forms dents due to the extrusion of pointed soil particles. The addition of nano-silicon dioxide not only fills the pores of the cement soil, but also promotes cement hydration, generates more and denser calcium silicate gel embedded in the fiber surface and its dents, thereby effectively preventing the sliding recombination of soil particles and further increasing the roughness of the fiber surface. The mechanical interlocking effect between the fiber and the matrix effectively prevents the fiber from being pulled out and broken under the action of tensile and compressive stress, thereby significantly improving the compressive strength, residual strength, crack resistance and seawater corrosion resistance of the cement soil. In addition, polyvinyl alcohol fiber is hydrophilic, and its surface contains polar groups, such as carboxyl (-COOH) and hydroxyl (-OH), which can adsorb water molecules and form ionic bonds with calcium ions. Therefore, the interfacial shear failure of polyvinyl alcohol fiber mainly involves two forces: one is the friction force between the fiber and the cement soil matrix, and the other is the mechanical force of breaking the chemical bonds between the fiber and the matrix. The above characteristics make it more suitable for use in combination with nano-silica than other fibers to improve the performance of cement soil.

[0044] The dry soil powder samples used in the following examples and comparative examples were collected from 15 meters underground at a construction site in Hongshan District, Wuhan City. The soil properties are similar to marine soft soil.

[0045] The average particle size of nano-silicon dioxide is 20nm and the specific surface area is 160-190m 2 / g, the length of the polyvinyl alcohol fiber is 6mm, the equivalent diameter is 16μm, and the density is 1.29g / cm 3 The mass ratio of sea salt to clean water in seawater is 35:1000 (usually filtering is required to remove insoluble impurities), the dispersant is polyvinyl pyrrolidone K30, and the cement is P.O42.5 silicate cement.

[0046] Example 1

[0047] (1) Dry the retrieved original soil and crush it through a 2 mm sieve to obtain dry soil powder with a particle size less than 2 mm.

[0048] (2) Mix 63.0% of the dry soil powder obtained in step (1), 1.2% of polyvinyl alcohol fiber, 1.9% of nano-silicon dioxide, 9.0% of cement and 0.2% of dispersant by mass percentage and pour them into a mixer and stir for 6-8 minutes until the mixture is uniformly mixed.

[0049] (3) Before adding polyvinyl alcohol fiber, it needs to be dispersed using ultrasonic vibration screen processing technology to improve the uniformity of polyvinyl alcohol fiber dispersion.

[0050] (4) Pour seawater (according to the mass content in Table 1) into the mixture in the mixer and continue stirring for 10-12 minutes until the mixture forms a uniform cement slurry.

[0051] (5) Pour the evenly mixed cement slurry into a cylindrical transparent plastic mold with a diameter of 39 mm and a height of 78 mm. During the grouting process, place the mold on a vibration table and keep it vibrating until the mold is full and the bubbles are removed.

[0052] (6) Mark the sample number and demould after curing at 20℃±2℃ for 48 hours to obtain the target product.

[0053] Example 2

[0054] (1) Dry the retrieved original soil and crush it through a 2 mm sieve to obtain dry soil powder with a particle size less than 2 mm.

[0055] (2) 65.0% of the dry soil powder obtained in step (1), 0.8% of polyvinyl alcohol fiber, 2.1% of nano-silicon dioxide, 9.0% of cement and 0.2% of dispersant were mixed by mass percentage and introduced into a mixer and stirred for 6-8 minutes until the mixture was uniformly mixed.

[0056] (3) Before adding polyvinyl alcohol fiber, it needs to be dispersed using ultrasonic treatment technology.

[0057] (4) Pour seawater (according to the mass content in Table 1) into the mixture in the mixer and continue stirring for 10-12 minutes until the mixture forms a uniform cement slurry.

[0058] (5) Pour the evenly mixed cement slurry into a cylindrical transparent plastic mold with a diameter of 39 mm and a height of 78 mm. During the grouting process, place the mold on a vibration table and keep it vibrating until the mold is full and the bubbles are removed.

[0059] (6) Mark the sample number and demould after curing at 20℃±2℃ for 48 hours to obtain the target product.

[0060] Example 3

[0061] (1) Dry the retrieved original soil and crush it through a 2 mm sieve to obtain dry soil powder with a particle size less than 2 mm.

[0062] (2) According to the mass percentage, 70.0% of the dry soil powder obtained in step (1), 1.0% of polyvinyl alcohol fiber, 2.2% of nano-silicon dioxide, 10.0% of cement and 0.2% of dispersant are mixed and introduced into a mixer and stirred for 6-8 minutes until the mixture is uniformly mixed.

[0063] (3) Before adding polyvinyl alcohol fiber, it needs to be dispersed using ultrasonic treatment technology.

[0064] (4) Pour seawater (according to the mass content in Table 1) into the mixture in the mixer and continue stirring for 10-12 minutes until the mixture forms a uniform cement slurry.

[0065] (5) Pour the evenly mixed cement slurry into a cylindrical transparent plastic mold with a diameter of 39 mm and a height of 78 mm. During the grouting process, place the mold on a vibration table and keep it vibrating until the mold is full and the bubbles are removed.

[0066] (6) Mark the sample number and demould after curing at 20℃±2℃ for 48 hours to obtain the target product.

[0067] Comparative Example 1

[0068] (1) Dry the retrieved original soil and crush it through a 2 mm sieve to obtain dry soil powder with a particle size less than 2 mm.

[0069] (2) Mix 63.0% of the dry soil powder obtained in step (1), 0.0% of polyvinyl alcohol fiber, 0.0% of nano-silicon dioxide, 9.0% of cement and 0.2% of dispersant by mass percentage and introduce them into a mixer and stir for 6-8 minutes until the mixture is uniformly mixed.

[0070] (3) Pour seawater (according to the mass content in Table 1) into the mixture in the mixer and continue stirring for 10-12 minutes until the mixture forms a uniform cement slurry.

[0071] (4) Pour the evenly mixed cement slurry into a cylindrical transparent plastic mold with a diameter of 39 mm and a height of 78 mm. During the grouting process, place the mold on a vibration table and keep it vibrating until the mold is filled and the bubbles are removed.

[0072] (5) Mark the sample number and demould after curing at 20℃±2℃ for 48 hours to obtain the target product.

[0073] Comparative Example 2

[0074] (1) Dry the retrieved original soil and crush it through a 2 mm sieve to obtain dry soil powder with a particle size less than 2 mm.

[0075] (2) 63.0% of the dry soil powder obtained in step (1), 1.2% of polyvinyl alcohol fiber, 0.0% of nano-silicon dioxide, 9.0% of cement and 0.2% of dispersant were mixed by mass percentage and introduced into a mixer and stirred for 6-8 minutes until the mixture was uniformly mixed.

[0076] (3) Before adding polyvinyl alcohol fiber, it needs to be dispersed using ultrasonic treatment technology.

[0077] (4) Pour seawater (according to the mass content in Table 1) into the mixture in the mixer and continue stirring for 10-12 minutes until the mixture forms a uniform cement slurry.

[0078] (5) Pour the evenly mixed cement slurry into a cylindrical transparent plastic mold with a diameter of 39 mm and a height of 78 mm. During the grouting process, place the mold on a vibration table and keep it vibrating until the mold is full and the bubbles are removed.

[0079] (6) Mark the sample number and demould after curing at 20℃±2℃ for 48 hours to obtain the target product.

[0080] Comparative Example 3

[0081] (1) Dry the retrieved original soil and crush it through a 2 mm sieve to obtain dry soil powder with a particle size less than 2 mm.

[0082] (2) 63% of the dry soil powder obtained in step (1), 0.0% of polyvinyl alcohol fiber, 2.2% of nano-silicon dioxide, 9.0% of cement and 0.2% of dispersant were mixed by mass percentage and introduced into a mixer and stirred for 6-8 minutes until the mixture was uniformly mixed.

[0083] (3) Pour seawater (according to the mass content in Table 1) into the mixture in the mixer and continue stirring for 10-12 minutes until the mixture forms a uniform cement slurry.

[0084] (4) Pour the evenly mixed cement slurry into a cylindrical transparent plastic mold with a diameter of 39 mm and a height of 78 mm. During the grouting process, place the mold on a vibration table and keep it vibrating until the mold is filled and the bubbles are removed.

[0085] (5) Mark the sample number and demould after curing at 20℃±2℃ for 48 hours to obtain the target product.

[0086] Comparative Example 4

[0087] (1) Dry the retrieved original soil and crush it through a 2 mm sieve to obtain dry soil powder with a particle size less than 2 mm.

[0088] (2) 63% of the dry soil powder obtained in step (1), 0.0% of polyvinyl alcohol fiber, 0.0% of nano-silicon dioxide, 9.0% of cement and 0.2% of dispersant were mixed by mass percentage and introduced into a mixer and stirred for 6-8 minutes until the mixture was uniformly mixed.

[0089] (3) Pour fresh water (according to the mass content in Table 1) into the mixture in the mixer and continue stirring for 10-12 minutes until the mixture forms a uniform cement slurry.

[0090] (4) Pour the evenly mixed cement slurry into a cylindrical transparent plastic mold with a diameter of 39 mm and a height of 78 mm. During the grouting process, place the mold on a vibration table and keep it vibrating until the mold is filled and the bubbles are removed.

[0091] (5) Mark the sample number and demould after curing at 20℃±2℃ for 48 hours to obtain the target product.

[0092] Comparative Example 5

[0093] (1) Dry the retrieved original soil and crush it through a 2 mm sieve to obtain dry soil powder with a particle size less than 2 mm.

[0094] (2) 63% of the dry soil powder obtained in step (1), 1.2% of polyvinyl alcohol fiber, 0.0% of nano-silicon dioxide, 9.0% of cement and 0.2% of dispersant were mixed by mass percentage and introduced into a mixer and stirred for 6-8 minutes until the mixture was uniformly mixed.

[0095] (3) Before adding polyvinyl alcohol fiber, it needs to be dispersed using ultrasonic treatment technology.

[0096] (4) Pour fresh water (according to the mass content in Table 1) into the mixture in the mixer and continue stirring for 10-12 minutes until the mixture forms a uniform cement slurry.

[0097] (5) Pour the evenly mixed cement slurry into a cylindrical transparent plastic mold with a diameter of 39 mm and a height of 78 mm. During the grouting process, place the mold on a vibration table and keep it vibrating until the mold is full and the bubbles are removed.

[0098] (6) Mark the sample number and demould after curing at 20℃±2℃ for 48 hours to obtain the target product.

[0099] Comparative Example 6

[0100] (1) Dry the retrieved original soil and crush it through a 2 mm sieve to obtain dry soil powder with a particle size less than 2 mm.

[0101] (2) 63% of the dry soil powder obtained in step (1), 0.0% of polyvinyl alcohol fiber, 2.2% of nano-silicon dioxide, 9.0% of cement and 0.2% of dispersant were mixed by mass percentage and introduced into a mixer and stirred for 6-8 minutes until the mixture was uniformly mixed.

[0102] (3) Pour fresh water (according to the mass content in Table 1) into the mixture in the mixer and continue stirring for 10-12 minutes until the mixture forms a uniform cement slurry.

[0103] (4) Pour the evenly mixed cement slurry into a cylindrical transparent plastic mold with a diameter of 39 mm and a height of 78 mm. During the grouting process, place the mold on a vibration table and keep it vibrating until the mold is filled and the bubbles are removed.

[0104] (5) Mark the sample number and demould after curing at 20℃±2℃ for 48 hours to obtain the target product.

[0105] Comparative Example 7

[0106] (1) Dry the retrieved original soil and crush it through a 2 mm sieve to obtain dry soil powder with a particle size less than 2 mm.

[0107] (2) 63% of the dry soil powder obtained in step (1), 1.2% of polyvinyl alcohol fiber, 1.9% of nano-silicon dioxide, 9.0% of cement and 0.2% of dispersant were mixed by mass percentage and introduced into a mixer and stirred for 6-8 minutes until the mixture was uniformly mixed.

[0108] (3) Before adding polyvinyl alcohol fiber, it needs to be dispersed using ultrasonic treatment technology.

[0109] (4) Pour fresh water (according to the mass content in Table 1) into the mixture in the mixer and continue stirring for 10-12 minutes until the mixture forms a uniform cement slurry.

[0110] (5) Pour the evenly mixed cement slurry into a cylindrical transparent plastic mold with a diameter of 39 mm and a height of 78 mm. During the grouting process, place the mold on a vibration table and keep it vibrating until the mold is full and the bubbles are removed.

[0111] (6) Mark the sample number and demould after curing at 20℃±2℃ for 48 hours to obtain the target product.

[0112] Comparative Example 8

[0113] (1) Dry the retrieved original soil and crush it through a 2 mm sieve to obtain dry soil powder with a particle size less than 2 mm.

[0114] (2) 60% of the dry soil powder obtained in step (1), 2.0% of polyvinyl alcohol fiber, 1.0% of nano-silicon dioxide, 10.0% of cement and 0.2% of dispersant were mixed by mass percentage and introduced into a mixer and stirred for 6-8 minutes until the mixture was uniformly mixed.

[0115] (3) Before adding polyvinyl alcohol fiber, it needs to be dispersed using ultrasonic treatment technology.

[0116] (4) Pour seawater (according to the mass content in Table 1) into the mixture in the mixer and continue stirring for 10-12 minutes until the mixture forms a uniform cement slurry.

[0117] (5) Pour the evenly mixed cement slurry into a cylindrical transparent plastic mold with a diameter of 39 mm and a height of 78 mm. During the grouting process, place the mold on a vibration table and keep it vibrating until the mold is full and the bubbles are removed.

[0118] (6) Mark the sample number and demould after curing at 20℃±2℃ for 48 hours to obtain the target product.

[0119] Comparative Example 9

[0120] (1) Dry the retrieved original soil and crush it through a 2 mm sieve to obtain dry soil powder with a particle size less than 2 mm.

[0121] (2) 60% of the dry soil powder obtained in step (1), 0.5% of polyvinyl alcohol fiber, 2.5% of nano-silicon dioxide, 9.0% of cement and 0.2% of dispersant were mixed by mass percentage and introduced into a mixer and stirred for 6-8 minutes until the mixture was uniformly mixed.

[0122] (3) Before adding polyvinyl alcohol fiber, it needs to be dispersed using ultrasonic treatment technology.

[0123] (4) Pour seawater (according to the mass content in Table 1) into the mixture in the mixer and continue stirring for 10-12 minutes until the mixture forms a uniform cement slurry.

[0124] (5) Pour the evenly mixed cement slurry into a cylindrical transparent plastic mold with a diameter of 39 mm and a height of 78 mm. During the grouting process, place the mold on a vibration table and keep it vibrating until the mold is full and the bubbles are removed.

[0125] (6) Mark the sample number and demould after curing at 20℃±2℃ for 48 hours to obtain the target product.

[0126] The cement soil samples prepared in Examples 1-3 and Comparative Examples 1-9 were subjected to unconfined compressive strength tests, and the performance parameters are shown in Table 1:

[0127] Table 1 Performance parameter results of unconfined compressive strength of cement soil samples of Examples 1-3 and Comparative Examples 1-9 after 28 days

[0128]

[0129] The experimental results show that the brittleness of cement soil can be significantly improved by adding polyvinyl alcohol fibers. In Example 1, the unconfined compressive strength of cement soil without nano-silica and polyvinyl alcohol fibers was 1.91MPa, and brittle failure occurred; in Example 2, the unconfined compressive strength of cement soil with only 1.2% polyvinyl alcohol fibers added was 2.55MPa, and no brittle failure occurred, which was 33.5% higher than that in Example 1; in Example 3, the unconfined compressive strength of cement soil with only 2.2% nano-silica added was 3.63MPa, and brittle failure occurred, which was 90.1% higher than that in Example 1.

[0130] The unconfined compressive strength of the composite cement soil mixed with 1.2% polyvinyl alcohol fiber and 1.9% nano-silicon dioxide in Example 1 is 5.02 MPa without brittle failure, and the growth rate is 162.8% compared with Comparative Example 1; the unconfined compressive strength of the composite cement soil mixed with 0.8% polyvinyl alcohol fiber and 2.1% nano-silicon dioxide in Example 2 is 5.09 MPa without brittle failure, and the growth rate is 166.5% compared with Comparative Example 1; the unconfined compressive strength of the composite cement soil mixed with 1.0% polyvinyl alcohol fiber and 2.2% nano-silicon dioxide in Example 3 is 5.23 MPa without brittle failure, and the growth rate is 173.8% compared with Comparative Example 1.

[0131] Comparative Examples 4-7 are comparison examples in which seawater is replaced with fresh water. In Comparative Example 4, the unconfined compressive strength of the cement soil without the addition of nano-silica and polyvinyl alcohol fibers is 2.85 MPa, and brittle failure occurs; in Comparative Example 5, the unconfined compressive strength of the cement soil with only 1.2% polyvinyl alcohol fibers added is 3.71 MPa, and no brittle failure occurs, and the growth rate is 30.2% compared with Comparative Example 4; in Comparative Example 6, the unconfined compressive strength of the cement soil with only 2.2% nano-silica added is 5.24 MPa, and brittle failure occurs, and the growth rate is 83.9% compared with Comparative Example 4; in Comparative Example 7, the unconfined compressive strength of the composite cement soil with 1.2% polyvinyl alcohol fibers and 1.9% nano-silica added is 6.36 MPa, and no brittle failure occurs, and the growth rate is 123.2% compared with Comparative Example 4.

[0132] Comparative Examples 1 and 4 are both cement soils without the addition of nano-silica and polyvinyl alcohol fibers. The unconfined compressive strength of the cement soil in Comparative Example 1 prepared with seawater is 1.91 MPa, which is 33% lower than the unconfined compressive strength of the cement soil in Comparative Example 4 prepared with fresh water, which is 2.85 MPa.

[0133] Comparative Examples 2 and 5 are both cement soils mixed with only polyvinyl alcohol fibers. The unconfined compressive strength of the cement soil in Comparative Example 2 prepared with seawater is 2.55 MPa, which is 31.3% lower than the unconfined compressive strength of the cement soil in Comparative Example 5 prepared with fresh water, which is 3.71 MPa.

[0134] Comparative Examples 3 and 6 are both cement soils added with only nano-silicon dioxide. The unconfined compressive strength of the cement soil in Comparative Example 3 prepared with seawater is 3.63 MPa, which is 30.7% lower than the unconfined compressive strength of the cement soil in Comparative Example 6 prepared with fresh water, which is 5.24 MPa.

[0135] Comparative Examples 8-9 are not composite cement soils prepared in the best ratio. The unconfined compressive strength is improved compared with Comparative Example 1, but there is a gap compared with Examples 1-3.

[0136] The present invention determines the optimal ratio of fiber and nano-silicon dioxide through a large number of experiments to avoid affecting the performance of the combined application of the two due to excessive or too little addition. When the amount of polyvinyl alcohol fiber added is too much, due to insufficient hydration products, it is difficult for the fiber to form an effective bond with the cement soil matrix, and the fibers are prone to agglomeration, thereby limiting the full play of the fiber function. Too little addition of polyvinyl alcohol fiber will result in the difficulty of significantly improving the crack resistance of the composite cement soil. When the amount of nano-silicon dioxide added is too much, although the mechanical strength is improved, the increase is low, and the improvement of the crack resistance of the composite cement soil is not obvious, and the application effect is limited. If the amount of nano-silicon dioxide added is too little, it is difficult to generate enough hydration products to fill the defective pores of the cement soil, and it is difficult for the fiber and the cement soil matrix to form a firm mechanical linkage, resulting in the advantage of the combined application of the two being not significant. The strength growth rate of the composite cement soil prepared by nano-silicon dioxide and polyvinyl alcohol fiber can exceed the sum of the growth rates of the single fiber-doped cement soil and the single nano-doped cement soil. Only by using the material with the optimal dosage determined by the present invention and the corresponding preparation method can the best curing effect be achieved.

[0137] In the present invention, the unconfined compressive strength of the composite cement soil prepared by seawater in Example 1 is 5.02MPa, which is 6.36MPa compared to the unconfined compressive strength of the composite cement soil prepared by fresh water in Comparative Example 7, and the strength is reduced by 21.0%. However, fresh water resources are extremely scarce in remote coastal areas and island reef areas. Although the fresh water strength is slightly higher, the long-distance transportation of fresh water not only significantly increases the cost, but also increases energy consumption, and requires the establishment of a temporary water supply system, thereby further increasing the project cost. The experimental data show that the combined application of nano-silicon dioxide and polyvinyl alcohol fiber in the present invention has the best effect. The composite cement soil prepared by seawater has a stronger unconfined compressive strength than ordinary cement soil. The unconfined compressive strength of the composite cement soil prepared by seawater is the smallest compared to the unconfined compressive strength of the composite cement soil prepared by fresh water. The unconfined compressive strength of the composite cement soil prepared by seawater in the present invention is not much different from that of the composite cement soil prepared by fresh water. Therefore, relative to the preparation of composite cement soil with fresh water, the present invention has significant economic benefits. In addition, the growth rate of the composite dosage is greater than the sum of the growth rates of each single dosage. The synergistic effect of nano-silica and polyvinyl alcohol fiber significantly enhances the mechanical properties, crack resistance and seawater corrosion resistance of cement soil, and effectively inhibits the brittle failure of cement soil, enabling it to be used in coastal soft soil foundation reinforcement projects in a long-term and stable manner.

[0138] It will be easily understood by those skilled in the art that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A composite cement soil prepared from seawater, nano-silicon dioxide and polyvinyl alcohol fiber, characterized in that: The raw materials of composite cement soil include, by mass percentage: dry soil powder 63%-70%, silicate cement 9%-10%, nano silicon dioxide 1.8%-2.2%, polyvinyl alcohol fiber 0.6%-1.2%, dispersant 0.2% and seawater 16.4%-25.4%.

2. The composite cement soil according to claim 1, characterized in that: The particle size of the nano silicon dioxide is 20±5nm and the specific surface area is 160-190 m² / g.

3. The composite cement soil according to claim 1, characterized in that: The length of the polyvinyl alcohol fiber is 6±1 mm, the equivalent diameter is 16±1 µm, and the density is 1.29±0.1 g / cm 3 .

4. The composite cement soil according to claim 1, characterized in that: The mass ratio of sea salt to water in the seawater is (32-38):1000.

5. The composite cement soil according to claim 1, characterized in that: The dispersant is polyvinyl pyrrolidone K30; And / or, the silicate cement is P.O42.5 silicate cement.

6. The composite cement soil according to claim 1, characterized in that: The dry soil powder is obtained by spreading the soil sample collected at a depth of 15±1m underground evenly and placing it outdoors for natural evaporation for 40-50 hours. After natural evaporation, the soil sample is crushed and placed in an oven at 105±5°C for drying for 20-30 hours, then taken out and cooled, and sieved through a 2 mm sieve to obtain dry soil powder.

7. A method for preparing a composite cement soil prepared from seawater, nano-silicon dioxide and polyvinyl alcohol fiber according to any one of claims 1 to 6, characterized in that: The preparation steps are as follows: (1) Weigh dry soil powder, polyvinyl alcohol fiber, nano-silicon dioxide, cement and dispersant according to the proportion, and then stir in a mixer until the mixture is uniform; (2) Weighing the required mass of seawater, pouring it into the mixture in the mixer, and continuing to stir until the mixture forms a uniform cement slurry; (3) pouring the evenly mixed cement slurry into the mold. During the grouting process, the mold is placed on a vibration table to keep vibrating until the mold is filled with cement slurry and bubbles are removed; (4) After curing at 20°C ± 2°C for 48 hours, demoulding is performed to obtain composite cement soil.

8. The preparation method according to claim 7, characterized in that: The mold is a cylindrical transparent plastic mold with a diameter of 39 mm and a height of 78 mm.

9. The preparation method according to claim 7, characterized in that: The polyvinyl alcohol fibers are dispersed by using ultrasonic vibration screen processing technology before being added.

10. An application of the composite cement soil prepared by seawater, nano-silicon dioxide and polyvinyl alcohol fiber according to any one of claims 1 to 6, characterized in that: Used for the preparation of coastal transportation roadbeds and pile foundations in coastal areas and island and reef areas.

Citation Information

Patent Citations

  • Preparation method of seawater mixed cement soil

    CN103539389B

  • Composite curing agent for deep stirring of high-water-content soft soil foundation and preparation method of composite curing agent

    CN114292080A

  • High performance cement soil and preparation method thereof

    CN103833297A

  • Ultra-high performance concrete mixed with seawater and prepared from full coral aggregate and preparation method thereof

    CN111620620A

  • Seawater corrosion resistant nano cement soil and preparation method thereof

    CN112851247A